2013
DOI: 10.1242/jeb.086991
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational long-distance communication in the termitesMacrotermes natalensisandOdontotermessp.

Abstract: ) of the signal without decrement over distances of several metres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…However, it is necessary to know that we can not accurately identify the termite acoustic signal delivered by its activity. Interesting facts about the termite behavior is alarm signal for intraspecific communication; Hager and Kirchner [48] reported that the velocity of propagation of individual vibrational signals in the nest substrate was found to be about 130 m s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to know that we can not accurately identify the termite acoustic signal delivered by its activity. Interesting facts about the termite behavior is alarm signal for intraspecific communication; Hager and Kirchner [48] reported that the velocity of propagation of individual vibrational signals in the nest substrate was found to be about 130 m s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The galleries have physical features that promote vibrational communication and are used as channels for long-distance communication (Hager and Kirchner, 2013). A variety of predators are of potential danger to foraging termites (Longhurst et al, 1978;Huey and Pianka, 1981;Redford, 1984;Kok and Hewitt, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Each pulse arises from a single tap of the termite's head against the ground. The number of pulses per signal varies between five and 22 (Hager and Kirchner, 2013). Nestmates are extremely sensitive to these vibrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic signals can be produced by simple termite activities; for instance, when termites are feeding and moving in the wood, they generate acoustic signals. Acoustic signals can also be produced by termites as alarm signals through head banging to the wood (Hager & Kirchner, 2013). Farkhanda (2013) proposed that biosensor devices could be a combination of several factors, such as temperature, moisture, movement, feeding and behavior of the termites, in the sensing technology.…”
mentioning
confidence: 99%